2012
DOI: 10.1007/s00268-012-1659-0
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Care in Africa: A Status Report From Botswana, Guided by the World Health Organization’s “Guidelines for Essential Trauma Care”

Abstract: Background Trauma represents a significant and increasing challenge to health care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…Traumatic injuries pose a significant and increasing challenge to healthcare systems worldwide. 1 According to the World Health Organisation (WHO), traumatic injuries are one of the main causes of mortality in the world, with 90% of the injuries estimated to occur in low-and middle-income countries. 2 A large number of traumatic injuries are orthopaedic in n ature.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injuries pose a significant and increasing challenge to healthcare systems worldwide. 1 According to the World Health Organisation (WHO), traumatic injuries are one of the main causes of mortality in the world, with 90% of the injuries estimated to occur in low-and middle-income countries. 2 A large number of traumatic injuries are orthopaedic in n ature.…”
Section: Introductionmentioning
confidence: 99%
“…A 2012 study on trauma care capacity in Botswana, a critical sector of the healthcare system for RTCs, found that hospitals have been developing physical resources and clinical expertise for trauma care, but trauma team organization, training activities, and plans for trauma care were absent. 23 This indicates that essential trauma care guidelines need to be applied to improve trauma care capabilities essential for care of those in RTCs. 23 …”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] The need to improve trauma care for RTIs in LMICs is widely recognized, but limited progress has been made thus far. [22,23] One limitation of this cross-sectional analysis is that it focused on hospitals located near the main north-south highway in Malawi.…”
Section: Discussionmentioning
confidence: 99%